Thermal Conductivity and Flexural Strength of Two-Step Hot-Pressed SiC Ceramics. Issue 1 (2nd January 2022) - Li, Jingren; Lu, Wenzhong; Jiang, Hai
Abstract : Effects of two-step hot-pressing on microstructure, thermal conductivity and flexural strength of silicon carbide (SiC) ceramics were investigated. A novel combination of aluminium nitride (AlN), La2 O3 and LaF3 was employed as sinter additives in this study. SiC ceramics prepared through both one-step (OS samples) and two-step (TS samples) hot-pressing method exhibited high relative densities. Compared with OS samples, the TS samples yielded finer microstructures with both higher thermal conductivities and flexural strengths. Impedance spectroscopy analysis was employed to reinforce the investigation on thermal conductivity variations in different samples. According to the analysis results, TS samples exhibited higher fitting grain and grain boundary resistances, which stood for a lower concentration of vacancies, indicating that two-step hot-pressing is more beneficial to the elimination of defects and improvement of thermal conductivity in SiC ceramics. On the other hand, TS samples were strengthened by a combined effect of finer microstructure and formation of SiC-AlN solid solution, thereby obtained higher flexural strengths. Hence, the present study suggests that two-step hot-pressing is more favorable to the improvement of both thermal conductivity and flexural strength of SiC ceramics with AlN-La2 O3 -LaF3 additive combinations. GRAPHICAL ABSTRACT: UF0001